Respuesta :

25 = 25

25 - 4x = 15 - 3x + 10 - x
25 = (15 + 10) - 3x - x + 4x
25 = 25

Notice that the "x terms" all end up cancelling out, leaving just the constants, which sum to 25 on both sides of the equation.

Hope this helps!

Good luck

Answer:

25-4x=15- 3x+10-x is a tautology which is valid for all values of x.

Step-by-step explanation:

25 - 4x = 15 - 3x + 10 - x

Simplifying the Right hand side(RHS):

15+10 -3x - x = 25 - 4x

But the left side(LHS) is also 25 - 4x

So the two sides are equal for all values of x.

The left hand side and right hand side are two different ways of representing the same expression.

This is similar to saying 2=2 or expression such as 2x = x+x.

Such expressions are independent of the value of the unknown variable x.

Hence the equation can be considered a tautology.